Foreign language classroom anxiety: An applied study for EFL students in AL Farqadeen non-governmental university in Basra - Abdullah, Narjis Faris; Sheaan, Hadeel Khalid; Yousif, Hayder Yaqoob (Research Journal in Advanced Humanities, 2026)
Through a mixed-methods research approach to exploring foreign language classroom anxiety, this study focuses on intermediate-level Iraqi students studying English as a foreign language at a university that is not affiliated with the government and located in Basra Iraq. The study utilized the Foreign Language Classroom Anxiety Scale (FLCAS) and the International English Language Testing System (IELTS) Speaking Test, as well as semi-structured interviews, to ascertain anxiety levels, the types of presentation of anxiety when speaking, and how these presentational patterns affect their performance while speaking. Findings from the quantitative portion of the study showed that all three dimensions of FLCAS showed moderate to high rates of anxiety (e.g., Communication Apprehension, Test Anxiety, and Fear of Negative Evaluation). Communication Apprehension had the highest level of anxiety, followed by Test Anxiety, and then Fear of Negative Evaluation. There was a statistically significant negative correlation between speaking anxiety and speaking performance, which indicates a strong relationship that if students have higher levels of anxiety, then they will have lower scores on their IELTS Speaking Test. There was no statistically significant difference between male and female students regarding their anxiety levels. Multiple students expressed anxiety in different ways with respect to presentation (i.e., through hesitation patterns, different levels of stress, and interruptions in fluency). Each student experienced a unique anxiety profile (i.e., confident speakers with little to no visual indicators of being anxious compared to individuals with significant anxiety who displayed multiple signs of anxiety). The results provide valuable insight into the understanding of EFL speaking anxiety as well as the urgent need for intervention approaches that alleviate psychological obstacles in Iraqi English education. The results also emphasize that an understanding of both cognitive and emotional dimensions of language acquisition must be taken into account.